ANALISIS MANAJEMEN RISIKO AKAD PADA PEMBIAYAAN MUDHRABAH DI SEGMEN UMKM DI BANK SYARIAH INDONESIA KC JAMBI – GATOT SUBROTO - Eja Armaz; Refky Fielnanda; Mahathir Hefrianda (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the analysis of the Indonesian Islamic Bank (BSI) KC Jambi - Gatot Subroto regarding contract risk management in the distribution of mudharabah financing in the UMKM segment which is distributed to customers by Bank Syariah Indonesia. The purpose of this study was to find out how the role of the Indonesian Islamic Bank (BSI) KC Jambi - Gatot Subroto in analyzing the financing they channeled to customers greatly impacted Indonesian Islamic banks. The type of research method used is descriptive qualitative research on mudharabah contract financing in the UMKM segment at the Indonesian Islamic bank (BSI) Jambi - Gatot Subroto branch office regarding the distribution of mudharabah contract financing. It turns out that from the results of this study, the funds distributed were obtained by several factors that caused problems in financing mudharabah contracts in the UMKM segment such as internal and external factors, including internal factors such as inaccurate analysis, incorrectly predicting collateral or guarantees, and poor employee performance. good, then on external factors such as the global economy, natural disasters, declining sales levels and customers getting out of obligations during the contract. The results of this study are expected to be a reference and input for Bank Syariah Indonesia KC Jambi - Gatot Subroto in analyzing the risk of murabahah contract financing in the UMKM segment in the Indonesian Islamic bank KC Jambi - Gatot Subroto.